1993
DOI: 10.1021/bi00089a050
|View full text |Cite
|
Sign up to set email alerts
|

A noncovalent peptide complex as a model for an early folding intermediate of cytochrome c

Abstract: Horse heart cytochrome c is one of a small number of proteins for which the folding pathway has been elucidated in structural detail by pulsed hydrogen exchange and NMR. Those studies indicated that a partially folded intermediate with interacting N- and C-terminal helices is formed at an early stage of folding when most of the chain is still disordered. This report describes a peptide model for this early intermediate, consisting of a noncovalent complex between a heme-containing N-terminal fragment (residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
87
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 39 publications
(48 reference statements)
12
87
0
Order By: Relevance
“…Kinetic experiments detected pathway intermediates that were interpreted in these terms Baldwin 1982, 1990). In agreement, a range of structural experiments characterized partially folded forms, molten globules, and folded protein fragments believed to mimic specific kinetic folding intermediates (Oas and Kim 1988;Staley and Kim 1990;Wu et al 1993;Ptitsyn 1995;Chamberlain et al 1999;Feng et al 2005;Maity et al 2005). Structural information from hydrogen exchange and related methods found and characterized partially native-like intermediates and showed that they construct classical folding pathways (Roder et al 1988;Bai et al 1995;Chamberlain et al 1996;Fuentes and Wand 1998a,b;Xu et al 1998;Milne et al 1999;Chamberlain and Marqusee 2000;Chu et al 2002;Hoang et al 2002;Silverman and Harbury 2002;Yan et al 2002Yan et al , 2004Feng et al 2003Feng et al , 2005Krishna et al 2003aKrishna et al ,b, 2004Krishna et al , 2006Maity et al 2004Maity et al , 2005Cecconi et al 2005;Weinkam et al 2005).…”
Section: Discussionmentioning
confidence: 79%
“…Kinetic experiments detected pathway intermediates that were interpreted in these terms Baldwin 1982, 1990). In agreement, a range of structural experiments characterized partially folded forms, molten globules, and folded protein fragments believed to mimic specific kinetic folding intermediates (Oas and Kim 1988;Staley and Kim 1990;Wu et al 1993;Ptitsyn 1995;Chamberlain et al 1999;Feng et al 2005;Maity et al 2005). Structural information from hydrogen exchange and related methods found and characterized partially native-like intermediates and showed that they construct classical folding pathways (Roder et al 1988;Bai et al 1995;Chamberlain et al 1996;Fuentes and Wand 1998a,b;Xu et al 1998;Milne et al 1999;Chamberlain and Marqusee 2000;Chu et al 2002;Hoang et al 2002;Silverman and Harbury 2002;Yan et al 2002Yan et al , 2004Feng et al 2003Feng et al , 2005Krishna et al 2003aKrishna et al ,b, 2004Krishna et al , 2006Maity et al 2004Maity et al , 2005Cecconi et al 2005;Weinkam et al 2005).…”
Section: Discussionmentioning
confidence: 79%
“…For example, in cyt c folding, the first-formed PUF (blue foldon folded, Fig. 1B) is more stable than the unfolded state by almost 3 kcal/mol in free energy (60), even though the isolated blue foldon is much less stable (61,62). In RNase H folding the first two foldons seem unlikely to be stable in isolation (see model in Fig.…”
Section: Results and Considerationsmentioning
confidence: 99%
“…Low and high pH (coupled with high ionic strength), low concentrations of guanidine and urea, and even various organic solvents have all been used to partially unfold proteins. The second approach studies the solution conformation and interactions of protein fragments (Brown and Klee, 1971;Baldwin, 1986;Sancho eta/., 1992;Wu et al, 1993;Waltho et al, 1993). The third approach uses quenched-flow, stopped-flow, or some other kinetic method to study the folding transients in real time (Ptitsyn, 1987;Kuwajima, 1989;Barrick and Baldwin, 1993;Baldwin, 1993;C.…”
Section: Introductionmentioning
confidence: 99%